Olga Musiiachenko. Music environment of Kyiv as an element of tourist image of the city in the second half of the XIX – early XX centuries - Musiiachenko, Olga (Young Scholars Grinchenko – Seton International Journal, 2021)
Abstract. The article is devoted to the use of components of the musical environment in the tourist image of Kyiv. We have analyzed the music environment of Kyiv in the second half of the 19th – early 20th centuries and the potential of using this information in forming the tourist image of Kyiv. We have examined the examples of using historic events and significant persons in forming the tourist image of cities and their tourism branding. We have suggested using the elements of the music environment, such as those that show the peculiarities and atmosphere of the time period (traditional culture, church and academic music), in forming the tourist image of Kyiv. Special attention was paid to the importance of popularization of prominent musicians of Kyiv who could become iconic figures associated with our city in the eyes of the tourists, such as Mykola Lysenko, a brilliant composer, musician, and civil activist, or Oleksandr Koshyts, a conductor whose memoirs paint the portrait of pre-revolutionary Kyiv and the place music used to hold in the lives of its citizens. In many memoirs about Mykola Lysenko we can see him as an extremely charismatic and witty person. Oleksandr Koshyts shared funny stories from the lives of seminarians and students of Kyiv Theological Academy. Oleksandr Koshyts offered serious reflections on the geopolitical and social situation of his day. He also told us what dances young people loved in the late 19th – early 20th centuries (mazurka was in vogue), what the rules of etiquette were like, what Ukrainian songs people were singing when going on walks, how they danced Hopak in the middle of the night at Vozdvyzhenka. Oleksandr Koshyts also reflected on the influence of the First Russian Revolution and World War I on music life, as well as on the importance of music in the lives of the Ukrainians who at the time were living under the Russian Empire. We also present our experience in using music elements during the development of theatrical excursions in Kyiv. It would be worthwhile to integrate more musical components into the tourist image of Kyiv, which would reflect the color and history of the city, as well as a characteristic combination of traditional culture, spiritual music and global trends. The second half of the 19th – early 20th centuries. contains many such materials: creative academic groups, traditional musicians, amateur performance, as well as interesting figures of Kyiv musicians, through whose activities you can feel the problems and atmosphere of that period. Keywords: music environment, music environment of Kyiv, image of a city, tourist image of a city, the second half of the 19th – early 20th centuries.